Focus teaching strategies to develop listening skill in attention deficit hyperactive disorder efl student - Robalino Pérez, José Andrés (2016)
The principal objective of this investigative work was to analyze focus teaching strategies to develop listening skill in attention deficit hyperactive disorder EFL student (henceforth ADHD). This investigation was qualitative because it permits to study the behavior and human habits. It was used a case study in this investigation and it was applied instruments such as: a checklist, surveys, and questionnaires. These data tools were validated and let the research to get real information to be analyzed. The main findings were the following: First, it was applied a psycho-pedagogical indicator (Check list) in order to get more information about this deficit. So, it showed that the student is not very talkative in class, constantly stand up, and cannot manage their attention in class. The student also does not finish on time the assigned tasks. She is very forgetful and she cannot sit still for short periods of time. She shows difficulty in attention, etc. Second, through a listening diagnose was evidence that the student that will call FS4ADHD get one of the lowest qualifications. The rest of the students obtained excellent scores; finally, a questionnaire was socializing with the objective to assess Teachers’ knowledge of Attention Deficit Hyperactive Disorder. The results permitted to find that teachers unknown strategies to develop listening skill. What is more, they are not familiarized with ADHD features. They do not have any information to identify this deficit in the students, and they have never had any ADHD training.